Can employment in a café change Clientele Attitude towards the staff when they are Persons with Mental Illness?. (May 2022) - Gandhi, Sailaxmi -; Jayaraman, Sangeetha; Sivakumar, Thanapal; John, Annie P; Joseph, Anoop; Prathyusha, Parthipulli Vasuki
Background: Clientele's attitude toward Persons with Mental Illness (PwMI) changes over a period of time. The aim of this study was to explore and understand how and whether perception about PwMI changes when they are seen working like persons without mental illness among those availing services of ROSes café at NIMHANS, Bengaluru. Methods: The descriptive research design was adopted with purposive sampling. Community Attitude toward Mentally Ill (CAMI) a self -administered questionnaire of was administered to measure the clientele attitude towards staff with mental illness in ROSes Café (Recovery Oriented Services). A total of 256 subjects availing services from the ROSes café recruited in the study. Chi-square and Mann–Whitney U test was computed to see the association and differences on selected variables. Results: The present study results showed that subjects had a positive attitude seen in health care professionals in the domains of benevolence (BE) (28.68 ± 3.00) and community mental health ideology (CMHI) (31.53 ± 3.19), whereas non-health care professionals had showed negative attitude in the domain of authoritarianism (AU) (30.54 ± 3.42) and social restrictiveness (SR) (30.18 ± 3.05). Education, employment, marital, income, and working status were significantly associated with CAMI domains. Conclusion: PwMI also can work like people without mental illness when the opportunities are provided. The community needs to regard mental illness in the same manner as chronic physical illness diabetes mellitus and allow PwMI to live a life of dignity by creating and offering opportunities to earn livelihood which would help them recover with their illnesses.